Rapid ECG interpretation - Khan, M. I. Gabriel (Human Press, 2017)
Basic concepts -- Step-by-step method for accurate electrocardiogram interpretation -- P wave abnormalities -- Bundle branch block -- ST segment abnormalities -- Q wave abnormalities -- Atrial and ventricular hypertrophy -- T wave abnormalities -- Electrical axis and fascicular block -- Miscellaneous conditions -- Arrhythmias -- ECG board self-assessment quiz.